#### Answer

$L=CZ^2$

#### Work Step by Step

$\bf{\text{Solution Outline:}}$
To solve the given formula, $
Z=\sqrt{\dfrac{L}{C}}
$ for $
L
,$ square both sides and then use the properties of equality to isolate the needed variable.
$\bf{\text{Solution Details:}}$
Squaring both sides of the given formula results to
\begin{array}{l}\require{cancel}
(Z)^2=\left( \sqrt{\dfrac{L}{C}} \right)^2
\\\\
Z^2=\dfrac{L}{C}
.\end{array}
Since $\dfrac{a}{b}=\dfrac{c}{d}$ implies $ad=bc$ or sometimes referred to as cross-multiplication, the equation above is equivalent to
\begin{array}{l}\require{cancel}
Z^2(C)=1(L)
\\\\
CZ^2=L
\\\\
L=CZ^2
.\end{array}